Inequitable access for mentally ill patients to some medically necessary procedures - Kisley, S.; Smith, M.; Lawrence, David; Cox, M.; Campbell, L.; Maaten, S. (Canadian Medical Association, 2007)
Background: Although universal health care aims for equity in service delivery, socioeconomic status still affects death rates from ischemic heart disease and stroke as well as access to revascularization procedures. We investigated whether psychiatric status is associated with a similar pattern of increased mortality but reduced access to procedures. We measured the associations between mental illness, death, hospital admissions and specialized or revascularization procedures for circulatory disease (including ischemic heart disease and stroke) for all patients in contact with psychiatric services and primary care across Nova Scotia.Methods: We carried out a population-based record-linkage analysis of related data from 1995 through 2001 using an inception cohort to calculate rate ratios compared with the general public for each outcome (n = 215 889). Data came from Nova Scotia's Mental Health Outpatient Information System, physician billings, hospital discharge abstracts and vital statistics. We estimated patients' income levels from the median incomes of their residential neighbourhoods, as determined in Canada's 1996 census.Results: The rate ratio for death of psychiatric patients was significantly increased (1.34), even after adjusting for potential confounders, including income and comorbidity (95% confidence interval [CI] 1.29?1.40), which was reflected in the adjusted rate ratio for first admissions (1.70, 95% CI 1.67?1.72). Their chances of receiving a procedure, however, did not match this increased risk. In some cases, psychiatric patients were significantly less likely to undergo specialized or revascularization procedures, especially those who had ever been psychiatric inpatients. In the latter case, adjusted rate ratios for cardiac catheterization, percutaneous transluminal coronary angioplasty and coronary artery bypass grafts were 0.41, 0.22 and 0.34, respectively, in spite of psychiatric inpatients' increased risk of death.Conclusions: Psychiatric status affects survival with and access to some procedures for circulatory disease, even in a universal health care system that is free at the point of delivery. Understanding how these disparities come about and how to reduce them should be a priority for future research.